Reactivity of 2-aryl-1,3-dithiane anions towards neopentyl, neophyl and phenyl iodides. New evidence for an SRN1 mechanism - Oksdath Mansilla, Gabriela (2011)
The reactions of 2-(4-Z-phenyl)-1,3-dithiane anions (Z=H, OMe, Cl, CN) with neopentyl, neophyl and phenyl iodides were studied in DMSO, taking into consideration the effect of the Z substituent on the dithiane anions reactivity as well as on the product distribution. These substitution reactions proceed by an SRN1 mechanism with radicals and radical anions as intermediates. Two competitive pathways are possible for the radical anion of the substitution product, namely electron transfer (ET) to the substrate giving the substitution product and C-S bond fragmentation to yield a distonic radical anion. ET is the main pathway for the reactions between dithiane anions bearing electron-donor substituents and neopentyl or its analogue iodides affording the substitution products in moderate yields (41-53%). Copyright © 2011 John Wiley & Sons, Ltd.